PEMANFAATAN EKSTRAK KULIT JERUK DALAM MENGENDALIKAN ULAT Plutella xylostella TANAMAN KUBIS SKALA LABORATORIUM - Rasiska Tarigan; Fatiani Manik; Rina. C. Hutabarat (JURNAL AGROTEKNOSAINS, 2018)
Plutella xylostella is the main pest to attack cabbage plants. The farmers was to control the Plutella xylostella by using insecticides chemical so that it has effect a negative impact on the environment and human health. So that to control it by used of vegetable fungicides and that are environmentally friendly. The objective of this study was obtain the effect and benefits of several orange extractsskin to controlling Plutella xylostellaon cabbage by a laboratory scale. The experimental was conducted in the laboratory of pests and diseases in the experimental farm of Berastagi, Indonesian of Vegetable Research Institute in January-April 2018. The treatment was consisted based onl randomized complete design non factorial. The treatment was consisting of ten treatments and three replications, It is namely: k0: control / water, k1 : lime skin extract 10 ml / 1 l, k2: extract of lime skin 20 ml, k3: extract of lime skin 30 ml/1l, k4: extract of kaffir lime skin 110 ml / 1 l k5: extract of kaffir lime skin 20 ml / k6: extract of kaffir lime skin 30 ml / 1l, k7: extract of sweet orange peel 10 ml / 1l, k8: extract of sweet orange peel 20 ml / 1l, k9: extract of sweet orange peel 30 ml / 1l and repeated 3 times. The each treatment has 10 sample of caterpillar. The variables observed were the percentage of mortality, time of death and symptoms of death. The results showed that the extract orange skin was effective to controlling Plutella xylostellalarvae on 30 ml / 1l consentration. The kinds skin of extract orange was significant effect to controlling plutella xylostela larvae, the namely orange skin is neem extract with 10 ml/1l until 20 ml/1 l concentration